Pemahaman Siswa Kelas XI SMAN 4 Kota Pasuruan dalam Pembelajaran Ekonomi pada Studi Kasus Sengketa Merek Geprek Bensu - Yovita Eka wulandari; Shelvi Amalia Putri; Rizki Silvia; Iqbal Syarifudin; Firza Agung Prakoso (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the responses and levels of understanding of eleventh-grade students at SMA Negeri 4 Pasuruan City regarding trademark disputes, particularly the “Geprek Bensu” case. The research employs a descriptive quantitative approach, with data collected through questionnaires distributed to students as respondents. The questionnaire was designed to describe students’ understanding of the concept of trademarks, the benefits of trademark registration, and their views on the causes of trademark disputes. The results indicate that most students are familiar with the “Geprek Bensu” case and understand trademarks as a business identity and a means of product differentiation. The majority of respondents are also aware that trademark registration provides legal protection and exclusive rights to the trademark owner. However, students’ understanding of trademark law remains varied, as some respondents still associate trademark ownership with popularity alone. In addition, students demonstrate a positive attitude toward the importance of intellectual property education from an early stage through formal education. These findings emphasize the need to strengthen Intellectual Property Rights literacy at the secondary school level in order to enhance legal awareness and prevent trademark disputes in the future.